q-Fibonacci bicomplex and q-Lucas bicomplex numbers - Aydin, Fugen Torunbalci (BULGARIAN ACAD SCIENCE, 2022)
In the paper, we define the q-Fibonacci bicomplex numbers and the q-Lucas bicomplex numbers, respectively. Then, we give some algebraic properties of the q-Fibonacci bicomplex numbers and the q-Lucas bicomplex numbers.
Keywords: Bicomplex number; q-integer (q-number); Fibonacci number; Bicomplex Fibonacci number; q -Fibonacci number; Mathematics